LEESOLA: A Locally Made Energy Efficient Solar Tracking System for Home Use - Kommey, Benjamin; Tamakloe, Elvis; Jerry, Agbesi; Wassem, Darkwa; Elikem, Normenyo Gershon (Fakultas Teknik Elektronika dan Komputer Universitas Kristen Satya Wacana, 2024)
A solar tracking system is used to orient solar reflectors, photovoltaic panels, and other solar energy harvesting equipment toward the sun mainly to maximize energy output. The LEESOLA system offers an optimized way to increase the amount of energy produced by exposing the harvesting equipment to the sun’s rays. This project is a crucial step towards a more sustainable future and reducing the reliance of humans on traditional energy sources. The system architecture of the LEESOLA solar tracker consists of a microcontroller-based control unit, an ultra-violet (UV) sensor module, motor drivers and PV panels. The UV sensor module detects the location of the sun and sends signals to the control unit. The control unit then passes signals to the motor drivers to introduce a change in the position of the solar panels. The control unit makes use of a suitable algorithm for keeping track of the location of the sun throughout the day and changes the angle of the PV panels accordingly. The UV sensor module makes use of essential optoelectronic components such as photodiodes or phototransistors to detect the position of the sun accurately. As a measure of eliminating any occurrence of misalignment due to factors such as weather conditions, the system has a built-in feedback mechanism that actively monitors the solar panel’s position and adjusts the motor drivers to correct any misalignment. The proposed system obtained an improvement of about 69.29%, 59.41% and 184.96% mean percentage difference in the measured power readings for morning, afternoon, and evening durations respectively. Therefore, this LEESOLA system provided an all-rounded performance improvement over the limiting static methods.